Значення вивчення української мови (за професійним спрямуванням) для підготовки майбутнього фахівця - Зімонова, Ольга Володимирівна; Зимонова, Ольга Владимировна; Zimonova, Olha (My University, 2017)
UK: У даній статті особлива увага приділена значенню наукового перекладу під час вивчення дисципліни «Українська мова за професійним спрямуванням» у вищому навчальному закладі. Зроблено висновок, що застосування навчального перекладу тільки тоді принесе користь, коли проводитиметься систематично і в певній системі. Добір дидактичного матеріалу залежить, насамперед, від мети, яку ставить перед собою викладач. EN: Special attention to the value of scientific translations in the study course "Ukrainian language for professional orientation" in the university has been paid in this paper. It is concluded that the use of learning transfer only benefit when conducted systematically and in a certain system. Selection of didactic material depends primarily on the purpose, which poses a teacher. For it is thanks to this we fix a student literacy skills of correct speech, which he will use later in his career. The article gives examples of economic direction texts for translation and editing. The author devotes a matter of linguistic etiquette, which regulates the linguistic behavior and relationships between employees. There are also examples of tasks related to the topic. Etiquette appeal not only serve to establish contact with the audience. also used to dialohizatsiyi speech, increased attention in the professional environment but also important is proper and appropriate use of plug-words and phrases, careful using winged words and other phraseology. To be effective, business relationships necessary to navigate not only themselves but also those who encircle develop its own style of communication. So, respect for foreign language is sign language etiquette.
Importance of ukrainian languages studying (for professional purposes) to prepare future professionals
Keywords: грамотність; кодифікація; стилістика; наукове спілкування; мовленнєва культура; фахівець; науковий переклад; заняття; фахова мова; мовна компетенція; literacy; codification; style; scientific communication; speech culture; professional; scientific translation; occupation; professional language; language competence